2020
DOI: 10.6061/clinics/2020/e1507
|View full text |Cite
|
Sign up to set email alerts
|

Survival trends of patients with oral and oropharyngeal cancer treated at a cancer center in São Paulo, Brazil

Abstract: OBJECTIVE:We aimed to estimate the overall survival (OS) and conditional survival (CS) in patients diagnosed with oral and oropharyngeal squamous cell carcinoma (SCC) and to determine their survival trends. METHODS:The study included all consecutive patients treated at the A.C. Camargo Cancer Center for oral or oropharyngeal SCC between 2001 and 2012. Data were obtained from the Hospital Cancer Registry. OS and CS were analyzed using the Kaplan-Meier method to evaluate the probability of survival with Cox pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 31 publications
4
29
1
2
Order By: Relevance
“…However, some studies conducted in the Southeast and Northeast regions' capitals did not identify differences in survival between the sexes. [12,34,35] Clinical factors such as site of injury, histological type, staging of the disease, type of treatment, time between diagnosis and initiation of treatment, nutritional status, and HPV exposure, also in uence the survival of individuals with oral cancer, [4,12,14,34,36,37] which may justify the difference found in this study compared to other ndings in the literature. Another possible explanation is that the regular use of health services, speci cally by women, [8] which can enable early diagnosis, encounters barriers such as wrong diagnoses and erroneous and/or late referrals, which lead to late diagnosis, with consequent worsening of prognosis and survival.…”
Section: Discussionmentioning
confidence: 56%
“…However, some studies conducted in the Southeast and Northeast regions' capitals did not identify differences in survival between the sexes. [12,34,35] Clinical factors such as site of injury, histological type, staging of the disease, type of treatment, time between diagnosis and initiation of treatment, nutritional status, and HPV exposure, also in uence the survival of individuals with oral cancer, [4,12,14,34,36,37] which may justify the difference found in this study compared to other ndings in the literature. Another possible explanation is that the regular use of health services, speci cally by women, [8] which can enable early diagnosis, encounters barriers such as wrong diagnoses and erroneous and/or late referrals, which lead to late diagnosis, with consequent worsening of prognosis and survival.…”
Section: Discussionmentioning
confidence: 56%
“…The 5‐year survival rate from all types of HNC was about 61%. For each site, the 5‐year survival corresponded to and even exceeded the data of other Western countries 21–25 …”
Section: Discussionmentioning
confidence: 74%
“…For each site, the 5-year survival corresponded to and even exceeded the data of other Western countries. [21][22][23][24][25] As expected, there was a significant difference in OS between the periphery and the center in Israel for ages <65 in all types of HNC. This may indicate poor quality and/or less availability of treatment in the periphery, less awareness of risk behavior, or differences in patient's delay until a diagnosis is made.…”
Section: Discussionmentioning
confidence: 76%
“…This could explain this study’s findings that this group was shown as the costliest for males and females and is also the one with highest demand for hospitalisation hours, attendants, and ICU. Also, this highest incidence regions are anatomically more complex and, considering that most cases of oral cancer that reach treatment are in advanced stages [ 29 ], the high cost of cancers in these regions may be related to a greater demand for more complex multimodal and surgical treatments, integrating multi- professional teams (vascular microsurgery, plastic surgery) and requiring professionals specialised in long-term rehabilitation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%